Indirect costs : a guide for foundations and nonprofit organizations - Eden, Rick, 1954-; Lyon, David W.; Payne, Judith E., 1950-; Brink, Alan.; Rand eBooks (Santa Monica, CA : RAND, 1986)
Indirect costs are costs for activities that benefit more than one project and for which it is difficult to determine how much each project should pay. When a nonprofit organization applies to a foundation for support, misunderstandings concerning indirect cost policies can arise between grantmaker and grantseeker. This report is intended to help parties on both sides of the grantmaking process to better understand the policy issues associated with indirect costs. It examines the range of foundation and nonprofit concerns, practices, and policies regarding indirect costs; develops a common perceptual framework for understanding indirect costs; and provides guidelines for presenting and reviewing indirect costs in proposal budgets. The report is based on interviews with representatives of community, corporate, and private foundations and with representatives of various grant recipients, including service organizations, teaching colleges, research institutions and universities, and arts and performance groups.
"January 1986."
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Associations, institutions, etc. -- United States -- Costs; Endowments -- United States; Overhead costs; Electronic books